Implementasi Function Point Analysis Untuk Pengukuran Kualitas Situs (Studi Kasus: Alibaba.com) - Soetam Rizky Wicaksono; Pandyawan Kusumo Kresno Putro; Gracecilla Aprillia Immanuel (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
To find out about how complex and useful a software is, a measurement needs to be done toward the software itself to found its complexity and its usefulness. From few methods that used for measuring a software, Function Point Analysis is most popular method to do the measurement, which measures a software from its functionality. From this research, three factors that very decisive were calculated, those are Crude Function Points (CFP), Relative Complexity Adjustment Factor (RCAF), and the Function Point (FP) calculation itself. This software measurement marks its end of the research at the point of doing a single transaction with the application. The results that came out with the calculation are Crude Function Points (CFP) with 183, Relative Complexity Adjustment Factor (RCAF) with 31, and the Function Point (FP) itself with 175.86, which shows that this web-based application is quite complex.